(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
We investigate a two-relaxation-time (TRT) lattice Boltzmann algorithm with the asymptotic analysis technique. The results are used to analyze invariance properties of the method. In particular, we focus on time dependent Stokes and Navier-Stokes problems.